MEDIA PEMBELAJARAN VIDEO STOP MOTION DAN KETERAMPILAN MENULIS TEKS EKSPLANASI: PENELITIAN PRE-EKSPERIMEN DI KELAS VI SEKOLAH DASAR - Hekti Nurhapitasari; Dian Indihadi; Erwin Rahayu Saputra (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The aim of this research is to determine the influence of stop motion animation media on the explanatory text writing skills of grade VI students of SDN 2 Cibalanarik. The type of research used is quantitative research with pre-experimental methods. The design in this study uses a one group pretest-posttest design. The population in this study is all grade VI students of SDN 2 Cibalanarik which totals 31 students. The sample used was selected based on the saturated sample technique, which was 31 students. The data collection technique is carried out by conducting tests and assessment rubrics. The data analysis technique is carried out through descriptive statistics and inferential statistics, where for this inferential statistics 2 testing processes are carried out, including prerequisite tests including (normality test and homogeneity test) and parsial hypothesis test (t-test). The results of this study show that the use of stop motion animation media has a significant effect on the writing skills of grade VI students of SDN 2 Cibalanarik. This is evidenced based on the results of the hypothesis test (t-test) which shows that there is a tcount > ttable which is 15,423 > 2,042, based on the df value or the term of degree of freedom which amounts to 30 with a confidence level of 5%. Thus, it can be concluded that stop motion animastion media can have an influence on the writing skills of explanatory texts of grade VI students of SDN 2 Cibalanarik.